A Multichamber, Pressure-Based Test Method to Determine Wind Loads on Air-Permeable, Multilayer Cladding Systems - Miller, Connell Shamus; Kopp, Gregory A.; Morrison, Murray J.; Kemp, Gary; Drought, Nick (Frontiers in Built Environment, 2017)
Current standardized testing on air-permeable multi-layer cladding is inaccurate as one of the primary parameters for setting the peak net wind loads across the cladding is the external pressure gradient which is removed from all standardized testing. After implementing a latex barrier system, and examining the control strategy for the Pressure Loading Actuators, a multi-chamber airbox system for testing air-permeable multi-layer cladding is developed and compared to a benchmark study performed by the Insurance Research Lab for Better Homes. The results indicate that using multi-chamber, pressure-based, testing to obtain wind loads for air-permeable, multi-layer wall systems with flexible cladding is sufficiently accurate. This method also shows that eliminating temporal variations from the external pressures for easier standardized testing would provide fairly accurate results.